The role of a thermally sprayed CuNiIn underlayer in the durability of a dry-film lubricant system in fretting: a phenomenological model - Barman, K.; Shipway, P.H.; Voisey, K.T.; Pattinson, G. (Elsevier, 2018)
Dry film lubricant coatings (DFL) are employed to reduce friction and damage in highly loaded contacts. Metallic underlayers, e.g. CuNiIn, can be beneficial however, there is no detailed explanation of the mechanism. This work investigates the effect of CuNiIn on fretting of a MoS2-based DFL in a cylinder-on-flat contact with a fretting amplitude of 300 µm. Two test types were run: 1. DFL without CuNiIn; 2. DFL on the cylindrical sample and DFL with CuNiIn underlayer on the flat sample. The CuNiIn increased the system’s durability. A phenomenological model highlighting the important low friction and highly wear resistant interfacial material is developed. The increased durability is ascribed to the high roughness of the CuNiIn onto which the DFL was deposited.